Gambaran Pengetahuan, Sikap Dan Praktik Bilas Vagina Pada Wanita Usia Subur Tahun 2012 (Studi Deskriptif Di RT III RW VII Kelurahan Rangkah Kecamatan Tambaksari Surabaya) - Frida Syamsiana (2011)
This research used a descriptive qualitative study about the description of knowledge, attitude, and vaginal douche practice in fertile women. The Problem of this research is the large number of fertile age women who douche the vaginal with materials that can disturb their health. The purpose of this research is learning the description of knowledge, attitudes, and vaginal douche practice in fertile women at RT III RW VllI Kelurahan Rangkah Kecamatan Tambaksari Surabaya. The method of this research was collected with in-depth interviews and FGD (Focus Group Discussion) with 40 fertile women as the iriformant by using snowball sampling. The data result was analyzed by using interactive analysis model (data reduction, data display, and conclusions). The result of the research are (1) Most women in this research interpret vaginal douche as a way to clean the vagina using water and materials such as soap, Sirih leaves and toothpaste that they do by themself at home regularly since adolescent. (2) Informants reason to do the vaginal douche were because of the boost from the nearest, believe the myth that the drier vagina add pleasure to your partner, and feel some advantages. (3) Informants have secondary education levels, unemployment, age more than 35 years, and Java ethnic. (4) Bath soap was the material that used the most by women. (5) Informants drink herbal medicine from Manjakani fruit to prevent and to heal women health. (6) There was a problems that occurs after a routine vaginal douche with femininity soap.